The Correlation Between Digital Literacy And Scientific Literacy Abilities With Students’ Learning Outcomes On Chemistry Material In Everyday Life - Tutik Sri Wahyuni; Mochamad Abdi Rohman Firdaus; Ifah Silfianah (Universitas Lambung Mangkurat, 2024)
The development of science and technology in the 21st century demands the cultivation of literacy culture as an essential life skill. Digital literacy and scientific literacy are crucial literacy skills that need to be developed. Digital literacy emphasizes the ability to critically understand and use digital information, while scientific literacy involves a deep understanding of science and the ability to apply it in everyday life. The objectives of this study are to determine: (1) students’ digital literacy abilities; (2) students’ scientific literacy abilities; (3) students’ learning outcome criteria; (4) the correlation between digital literacy and learning outcomes; and (5) the correlation between scientific literacy and students’ learning outcomes on chemistry material in everyday life. This study employed a correlational research design with a quantitative approach. The subjects of the study consisted of 55 tenth-grade students from MAN 1 Nganjuk, selected using purposive sampling from a total population of 96 students. The data collection techniques included a digital literacy skills questionnaire, an essay test for scientific literacy, and a multiple-choice test for learning outcomes, each comprising 20 items. The instruments had been validated, with reliability values of 0.900, 0.854, and 0.863, respectively. The data analysis technique used descriptive statistics and the Spearman rho test. The results of the study showed that: (1) the average level of students’ digital literacy is categorized as “good” with a score of 76.87; (2) the level of scientific literacy is categorized as “good” with an average score of 68.09; (3) the average learning outcome score is 85.27, categorized as “very good”; (4) there is a correlation between digital literacy and learning outcomes, with a correlation coefficient of 0.464, categorized as “moderate”; and (5) the correlation between scientific literacy and students’ learning outcomes in chemistry is strong, with a correlation coefficient of 0.611.